The Diversity of the Morphometric Profiles of the Pore Space in Soddy-Podzolic and Gray Forest Soils of East European Plain - E. B. Skvortsova; V. A. Rozhkov; A. V. Yudina; N. A. Vasil’Eva (Бюллетень Почвенного института им. В.В. Докучаева)
Among the quantitative indices of the pore space, the morphometric data are characterized by the largest genetic specificity. The values of size, form and pore orientation, which form the morphometric profiles, reflect the vertical variability of the morphological composition of the soil pores. The computer analysis of the pore space in the thin sections of the soil from the main genetic layers showed lateral variability, and also the similarity and difference of morphometric profiles of the pore space in the soddy-podzolic and gray forest soils of European Russia within the range 0.2 mm < d < 2.0 mm. In order to assess the variability of the profiles of the pore space according to different morphometric indices and their comparison to each other we used method of multivariate statistics. The lateral variation of the profile distribution of the cracky roundish and horizontally (subhorizontally) oriented pores in the soddy-podzolic and gray forest soil is quite high (the most of variation coefficients exceed 15-20%). In both soils the diversity of the profile distributions of cracky and roundish pores is higher than that of pores with horizontal (subhorizontal) orientation. Comparing to the gray forest soil, the soddy-podzolic soil is generally characterized by the less expressed variation of profiles of the pore space according to the all investigated indices.